How To Identify Failing Companies Before It Is Too Late: Case Study Analysis On 5 Selected Failing Companies Based On Altman Model / Rakayah Hamdan - Hamdan, Rakayah (1996)
Business is a high risk activity and it is very hard for each companies to survive for a long-term period. However, it can be done by reviewing continually on the company financial statement as a tool to make decision and measurement on the company performance. These cannot be successfully done without evaluating other factors such as non-financial factor especially on the management ofthe company. With the usage ofthe financial statement analysis on 5 selected companies as a tool to predict company failure by using Z-Score Model and considering non-financial factor, both can provide meaningful information which can help company management or interested parties with regards to bankruptcy. It is hope that this case study will helps the users in predicting the company failure before it is occurred.